Nursing care at the hospital center in perioperative care (Research, Society and Development, 2023)
Objective: To identify in the scientific literature on nursing care in the hospital surgical center in perioperative care. Method: This is an integrative review of the Lilacs, BVS and SciELO databases. Data collection took place in October 2022, including articles from the period between 2017 and 2022. To collect data from the selected studies, a standardized form was used containing: study identification, authors, study objective, results and recommendations, and conclusions. Results: 572 articles were selected. Of these, only 4 articles met the inclusion criteria. Of the 4 selected studies, all were produced in Brazil from 2017 to October 2022. The studies included in this review highlighted the following nursing care: pre- and postoperative visits, nursing care in hypothermia, systematization of nursing care. Conclusion: This study contributed to assist in the updating of health professionals where the main nursing care found were the pre- and postoperative visit, nursing care in hypothermia, systematization of nursing care.